Improvement of an in-house ELISA for bovine paratuberculosis serology in Brazil - Marassi,Carla Dray (2005)
Paratuberculosis (Johne's disease) is a chronic enteritis in cattle caused by infection with Mycobacterium avium subsp. paratuberculosis (Map). In Brazil, few reports describe the isolation of the organism. The gold standard test for Map is its isolation from tissues or feces. Moreover, bacterial growth is slow and test results are available only after three to five months of incubation Furthermore, shedding of bacilli at levels detectable by fecal culture is irregular and does not occur during the early stages of infection, which compromises the sensitivity of this methodology. The most common immunological tests to identify Map infection are complement fixation test (CFT), agar gel immunodiffusion (AGID) and enzyme-linked immunoassay (ELISA). In Brazil, commercial ELISA kits are imported and too expensive to be used as part of diagnostic laboratorial routine. Apart from that, their use has not yet been approved in the country. The aim of the present study was to improve an original assay PPA-ELISA protocol established by our group, and to determine sensitivity and specificity of the modified test. In a first step, we introduced modifications that minimized plate-to-plate and between-well variations, thus making the test more stable and reliable. In the second part of this study, a panel of 106 sera samples was tested by this modified PPA-ELISA protocol in order to estimate its sensitivity and specificity. The new assay presented overall sensitivity of 76.9% and specificity of 70.0%. Our study demonstrated that this assay could be recommended as a valuable tool for diagnosis and control of paratuberculosis in Brazil and other developing countries.